Teaching in business administration: a customized process driven by technological innovations (Journal of Management and Business Education, 2020)
Three technological innovations are challenging higher education learning processes. This paper addresses the implications for these learning processes of interactive digital transformation, artificial intelligence, and content customization. These innovations involve three types of teaching and learning activity processes, digital learning, learning analytics and tailored learning. Our approach suggests relevant implications for carrying out teaching activities in the new scenario characterized by learning anywhere at any time. Furthermore, the digitalization process allows teachers to use data mining techniques to monitor students’ activity; this can be used as a basis for customizing delivered content. Last, a question agenda is proposed and further developments are examined based on the three parties involved in the learning process: students, teachers and delivered content.
Keywords: digital learning; learning analytics; tailored learning; artificial intelligence